The Formation and Stability of Recognition Memory: What Happens Upon Recall? - Davis, Sabrina; Poirier, Roseline; Renaudineau, Sophie; Poucet, Bruno; SAVE, Etienne; Laroche, Serge (Frontiers in Behavioral Neuroscience, 2010)
The idea that an already consolidated memory can become destabilised after recall and requires a process of reconsolidation to maintain it for subsequent use has gained much credence over the past decade. Experimental studies in rodents have shown pharmacological, genetic or injurious manipulation at the time of memory reactivation can disrupt the already consolidated memory. Despite the force of experimental data showing this phenomenon, a number of questions have remained unanswered and no consensus has emerged as to the conditions under which a memory can be disrupted following reactivation. To date most rodent studies of reconsolidation are based on negatively reinforced memories, in particular fear-associated memories, while the storage and stability of forms of memory that do not rely on explicit reinforcement have been less often studied. In this review, we focus on recognition memory, a paradigm widely used in humans to probe declarative memory. We briefly outline recent advances in our understanding of the processes and brain circuits involved in recognition memory and review the evidence that recognition memory can undergo reconsolidation upon reactivation. We also review recent findings suggesting that some molecular mechanisms underlying consolidation of recognition memory are similarly recruited after recall to ensure memory stability, while others are more specifically engaged in consolidation or reconsolidation. Finally, we provide novel data on the role of Rsk2, a mental retardation gene, and of the transcription factor zif268/egr1 in reconsolidation of object-location memory, and offer suggestions as to how assessing the activation of certain molecular mechanisms following recall in recognition memory may help understand the relative importance of different aspects of remodelling or updating long-lasting memories.